Use of different bivariate statistical landslide susceptibility methods: A case study of Khulekhani watershed, Nepal - Singh Pradhan, Ananta Man; Dawadi, Anurag; Kim, Yun Tae (Journal of Nepal Geological Society, 2012)
Available with full text.